Hepatocarcinoma Single Cell Migration on Micropatterned PDMS Substrates - Bin Zheng; Shu-Ling Hsieh; Chih-Chung Wu; Chun-Hsin Wu; Pei-Ying Lin; Chiung-Wen Hsieh; I-Tin Li; Yun-Shan Huang; Huay-Min Wang; Shuchen Hsieh (Nano Biomedicine and Engineering, 2011)
Cell migration influences many normal and pathological processes and is one of key issues addressed in cancer research studies. In this report, a plasma patterned polydimethylsiloxane (PDMS) substrate was used to selectively position hepatocarcinoma cells in order to characterize their migration behavior. We observed that cell mobility was directly related to the differentiation stage of the cells, with poorly-differentiated (SK-Hep-1) cells exhibiting higher mobility that well-differentiated (Hep-G2) cells. We propose that this difference occurs due to a loss of adhesion molecules presented at the apical membranes of the poorly-differentiated SK-Hep-1 cells, thereby reducing their adhesion to the surface. Our results provide new insight into the relationship between carcinoma cell differentiation grade and mobility. Further this experimental process may provide a simple and effective model for universal cell biology studies and applications in microsystems technology.